2019
DOI: 10.1002/smll.201901789
|View full text |Cite
|
Sign up to set email alerts
|

Control of Catalytic Activity of Nano‐Au through Tailoring the Fermi Level of Support

Abstract: Nanoparticles of noble metals dispersed on solid support have been extensively utilized for catalyzing chemical reactions for energy conversion, environmental remediation, and chemical industry for their remarkable catalytic performance. [1][2][3][4] To maneuver the catalytic performance of these materials, tremendous efforts have been focused on the control of metal nanoparticles, including size and shape, [5][6][7] composition, [8] and chemical ordering. [9] At the meantime, the influence of the support on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 50 publications
1
18
0
3
Order By: Relevance
“…Supported gold (Au) and palladium (Pd) nanoparticles are promising catalyst for this reaction [5][6][7]. Strategies have been developed to optimize the activity and selectivity of nanocatalysts, including size and shape control of nanometals [8,9], engineering the supports [10], or composition adjustment [3]. In particular, bimetallic nanoparticles are attracting intensive interests because of the improved catalytic properties deriving from the synergetic effects between two elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supported gold (Au) and palladium (Pd) nanoparticles are promising catalyst for this reaction [5][6][7]. Strategies have been developed to optimize the activity and selectivity of nanocatalysts, including size and shape control of nanometals [8,9], engineering the supports [10], or composition adjustment [3]. In particular, bimetallic nanoparticles are attracting intensive interests because of the improved catalytic properties deriving from the synergetic effects between two elements.…”
Section: Introductionmentioning
confidence: 99%
“…differences in particle size, morphology, structure, and even electronic properties [13][14][15]. Currently, most work on noble metal nanocatalyst is accomplished by bottom-up synthesis in solutions that generally contains step of reduction [10,16] or decomposition [14,17] of positive valent metal precursors at harsh conditions. For example, the conventional method mainly involves impregnation that usually needs thermal reduction to obtain metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, interactions with the oxide support significantly impact the electronic structures and in turn the catalytic performance of nanometals [21,22]. Recently, we have demonstrated that the electron exchange between the two phases is highly correlated with the Fermi level of the oxide support [23]. The electron density and Fermi level of oxides can be tailored by breaking the symmetry or stoichiometry of the crystal structure, such as defects engineering [24,25] or doping [26,27], resulting in changes in catalytic activity and activation energy of the catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been widely recognized that the support plays more roles than simply providing a surface area. Electronic interactions across the interface have a significant and direct impact on the catalytic activity of the metal nanocatalyst [4,5]. In this scenario, the quality of the metal-support interface is key in order to manipulate their performance even if the metal and the support are the same, as such an interaction can affect only the sites less than 1 nm away from the interface [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Electronic interactions across the interface have a significant and direct impact on the catalytic activity of the metal nanocatalyst [4,5]. In this scenario, the quality of the metal-support interface is key in order to manipulate their performance even if the metal and the support are the same, as such an interaction can affect only the sites less than 1 nm away from the interface [4,6]. However, metals are simply loaded on the support in most nanocatalysts prepared by conventional solution methods, limiting the metal-support interaction and weakening the metal stability in harsh conditions [7].…”
Section: Introductionmentioning
confidence: 99%